2019
DOI: 10.1016/j.hpb.2018.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemotherapy is associated with improved postoperative survival in specific subtypes of invasive intraductal papillary mucinous neoplasms (IPMN) of the pancreas: it is time for randomized controlled data

Abstract: Background: Very little is known about adjuvant chemotherapy for invasive Intraductal Papillary Mucinous Neoplasms (IPMNs) of the pancreas. The aim was to assess whether adjuvant chemotherapy affects survival. Methods: Retrospective evaluation of invasive IPMNs. Patients treated with surgery alone or followed by adjuvant chemotherapy were compared in terms of survival.Results: A total of 102 invasive IPMNs were analyzed. Median follow-up was 72 (5-318) months and 18.6% received adjuvant chemotherapy. Overall, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 34 publications
2
37
1
2
Order By: Relevance
“…No benefit on survival was noted in patients with stage I and/or node-negative disease (63). Similar results have been shown by Marchegiani and colleagues, suggesting that chemotherapy could confer a survival benefit mainly in patients with node-positive disease of the tubular subtype (64).…”
Section: Future Perspectivessupporting
confidence: 87%
See 1 more Smart Citation
“…No benefit on survival was noted in patients with stage I and/or node-negative disease (63). Similar results have been shown by Marchegiani and colleagues, suggesting that chemotherapy could confer a survival benefit mainly in patients with node-positive disease of the tubular subtype (64).…”
Section: Future Perspectivessupporting
confidence: 87%
“…Although these data seem to encourage adjuvant treatment for invasive IPMN, there is a large lack of consensus on chemotherapy regimens. Most patients are treated with gemcitabine alone, while only a few patients are treated with combined drug regimens (64). Moreover, variability in chemotherapy effects could be represented by different histologic subtypes of the invasive component.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…However, Leng et al suggested that adjuvant radiotherapy was not associated with the improved survival of patients with resected perihilar cholangiocarcinoma. Interestingly, even though adjuvant therapy has been confirmed to improve prognosis in MAC, our findings suggested that postoperative adjuvant chemotherapy was not significantly associated with the RFS and OS of HCM patients in the multivariate analysis. Future large prospective studies are needed to determine which patients are at high risk for adverse prognosis and who might, therefore, benefit from adjuvant therapy.…”
Section: Discussioncontrasting
confidence: 60%
“…В таблице приведены основные тактические положения этих рекомендаций. Тактика лечения ВПМО по рекомендациям Международной панкреатологической ассоциации (2017) и Европейским рекомендациям (2018) В рекомендациях IAP2017 признаками высокого риска малигнизации являются механическая желтуха, обусловленная опухолью, наличие в пределах кисты солидного компонента 5 мм и менее, накапливающего контраст, расширение главного ПП до 10 мм и более. Это абсолютные показания к операции.…”
Section: клинические рекомендации и тактика леченияunclassified
“…В то же время по данным G. Marchegiani и соавт. [46], адъювантная терапия увеличивает продолжительность жизни только при тубулярном подтипе карциномы и вовлеченности лимфатических узлов. Для формирования окончательных выводов требуется дальнейшее изучение этого вопроса.…”
Section: клинические рекомендации и тактика леченияunclassified